Controle de complacência em simuladores cranianos - Bezerra, Ítalo Gabriel (Universidade Federal de São Carlos, 2023)
Changes in intracranial pressure (ICP) are related to pathologies such as traumatic brain injury (TBI) and idiopathic intracranial hypertension (IIH). However, the direct access to the PIC, is complex and risky, since an invasive procedure is required to access the brain of patients, bringing the risk of infection and the need for a surgical center. Therefore, it is of great importance to develop technologies that can monitor the ICP in a non-invasive way. The central nervous system (CNS) has ICP autoregulation systems activated by changes in blood or fluid volume cerebrospinal fluid (CSF). The ratio between intracranial volume variation and ICP variation is called intracranial compliance (CIC). This project aimed to develop a compliance simulator to be applied in testing monitoring technologies of the ICP in a non-invasive way. This simulator used a PET bottle as the main element. In the development of this simulator, the behavior of pressure and complacency during infusions of water into the system. Complacency showed a tendency slightly decreasing linear. With test data from the cranial simulation system a complacency determinator was developed, a tool that relates complacency, the pressure, initial volume of water in the system, the initial volume of air and the infusion volume of water. The knowledge acquired in this project and the tool developed here will help researchers in more precise control of compliance during tests in simulators where it is necessary to know this parameter. In addition, the work carried out will help in the creation of more complex simulators.
Compliance control in cranial simulators
Keywords: Complacência; Simuladores; CIENCIAS EXATAS E DA TERRA::FISICA